Reactions of team teachers and selected freshmen students of Elpidio Quirino High School on the effects of team teaching - Phlisak, Sirikun 1947- ([Quezon City s.n.], 1973)
Twelve teachers and 200 freshmen did not differ in their reactions to team teaching practices in practical arts and home arts. Teachers opined that team teaching gave teachers more time to see each other and to share materials and information with each other, help each other in academic work, and to discuss observations on the effects of teaching and student problems. The students felt that team teaching gave teachers more time to cooperate in the evaluation of instruction, plan lessons together and interact with each other meaningfully. Poblems were met regarding inadequate instructional materials and facilities, ill-defined responsibilities, inadequate knowledge in preparing teaching units and instructional materials, oversized classes, and human relations.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Teaching teams